Struś - nowe źródło mięsa drobiowego. Właściwości technologiczne i wyroby z mięsa - Haraf, Gabriela (Ostrich- the New Source of Poultry Meat. Functional Traits and Value Added Ostrich Products, 2008)
The paper is a review on processing quality of ostrich meat and characteristics of value added ostrich products. Ostrich meat is characterized by high pH and water holding capacity and can be used as a processing meat. It is used for production among others emulsion - type meat products, hams and salami sausages. From the review it is known that value added ostrich products can compete successfully with similar types of products derived from other meat species. Furthermore, the chemical composition of ostrich meat (low fat and cholesterol content as well as high protein, iron and polyunsaturated fatty acids content) make, the ostrich products favourable from the nutritional point of view. More and more consumers have a concern for their diet from a health aspect, so the food industry should provide a wide range of healthy products, including the ostrich products, in response to this need. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 30, s. 24-33